Equity and Dignity in Maternity Care Provision in Canada, Finland and Iceland - Wrede, Sirpa (Can J Public Health, 2008)
OBJECTIVE: In recent decades, governments around the globe have been under pressure to create more efficient and effective health care systems. Research shows, particularly in middle- and low-income countries, that many of these neo-liberal policies that have been enacted have had a largely negative effect with regard to equitable health services for lower-income populations and dignified working conditions for health providers. In this paper we highlight recent reforms in health care in Canada, focusing on formal care during pregnancy and childbirth, and compare these to parallel developments in two Nordic countries–Finland and Iceland. METHOD: We draw upon secondary data sources and primary research findings. RESULTS: Our comparative analysis pays close attention to barriers in access to primary care services across the childbearing period for lower-income women in the three countries, as well as the factors that create poor working conditions for the predominantly female maternity care labour force. DISCUSSION: As Canada struggles to deal with the crisis in its maternity care system, it could learn from developments in Finland and Iceland that promote teamwork among primary health care professionals and high-quality care for lower-income populations.